NiCo-OH / FeOOH heterostructure nanosheet as well as preparation method and application thereof

By manufacturing NiCo-OH/FeOOH heterostructure nanosheet composite electrode based on corrosion and immersion engineering, the problem of difficult application of iron-based OER catalysts under high current conditions is solved, and high-activity and low-cost OER catalytic effect is achieved , exhibits excellent electrochemical properties and stability.

CN119194502APending Publication Date: 2024-12-27JILIN UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411375329.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing iron-based OER catalysts are difficult to apply under high current conditions, and most heterostructure synthesis processes are complex, high energy consumption, and lack low-cost and simple manufacturing methods.

Method used

Using a simple strategy based on corrosion and immersion engineering, Co-ZIF-L nanosheets were grown in situ on the substrate material by immersion method, and NiCo-OH nanosheets were synthesized with low temperature hydrothermal reaction, and NiCo-OH/FeOOH was soaked at room temperature to generate NiCo-OH/FeOOH Nanosheet composite material, used as composite electrodes for electrochemical water decomposition and analytical oxygen reaction.

Benefits of technology

It realizes high-active and low-cost OER catalysis in alkaline media, with an overpotential of 1000mA cm-2 with a current density of only 306mV, a Tafel slope as low as 38mV dec-1, and exhibits excellent stability in the 100h timing potential test. Better than commercial catalyst RuO2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194502A_ABST
    Figure CN119194502A_ABST
Patent Text Reader

Abstract

The invention relates to a NiCo-OH / FeOOH heterostructure nanosheet as well as a preparation method and application thereof. The NiCo-OH / FeOOH heterostructure nanosheet derived from MOF (Metal Organic Framework) is manufactured on the basis of a simple and convenient strategy of corrosion and soaking engineering. A heterostructure is constructed in the catalyst, so that the electronic structure of the catalyst can be adjusted, the adsorption energy of a reaction intermediate product can be optimized, and the catalytic activity of the catalyst can be remarkably improved. Due to the synergistic effect between nickel and cobalt, the iron heterostructure is introduced, so that the electro-catalytic performance of the transition metal compound in an alkaline solution can be further improved, and the purpose of improving the catalytic activity is achieved. The NiCo-OH / FeOOH nanosheet composite electrode material obtained by the invention has an ultrathin nanosheet structure, provides a larger electrochemical active region and abundant exposed active sites, and improves the dynamics and enhances the ion transmission due to the synergistic effect between NiCo-OH and FeOOH, thereby improving the intrinsic catalytic activity and enhancing the electrochemical activity. The electrode can be used as a catalytic electrode in electrochemical water desorption oxygen-desorption reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a heterostructure nanosheet and a preparation method and application thereof, and in particular to a simple strategy based on corrosion and immersion engineering to manufacture MOF-derived NiCo-OH / FeOOH heterostructure nanosheets and application thereof as a composite electrode in an electrochemical water-desorption oxygen reaction. Background Art

[0002] With the increasing requirements for low-carbon emission reduction, hydrogen energy as a zero-carbon energy carrier has received increasing attention, and green hydrogen production technology has also received widespread attention. Electrochemical water splitting is a sustainable and promising clean hydrogen production technology, especially under alkaline conditions, which has commercial applicability for large-scale hydrogen production. Water electrolysis consists of two half reactions, namely the hydrogen evolution reaction HER and the oxygen evolution reaction OER. Among them, OER is a complex four-electron transfer process with slow kinetics and requires higher energy, which has become a bottleneck restricting the overall energy efficiency improvement of green hydrogen production by water electrolysis. At present, the most effective OER catalysts are precious metals IrO2 and RuO2, but their high cost and scarcity severely limit their large-scale application. Therefore, it is urgent to develop highly active and cost-effective OER catalysts to reduce the cost of hydrogen production.

[0003] Iron-based compounds have attracted considerable attention due to their low price, abundant crustal abundance, and high OER activity in alkaline media. Among various iron-based materials, iron oxyhydroxide FeOOH is not only highly active for OER, but is also widely considered to be the true active species of iron-based OER electrocatalysts because a large amount of iron-based materials are hydroxylated and converted to FeOOH in OER experiments. However, FeOOH still has the potential for further improvement in terms of improving electrochemical activity, regulating active sites, and improving stability. To this end, combining two or more catalytic materials to construct heterostructures has been considered an effective strategy to improve catalytic activity. Electron transfer across the heterojunction can not only regulate the electronic structure of the catalyst, thereby improving the catalytic activity and optimizing the adsorption energy of the reaction intermediates; but also the conductivity and chemical stability of the heterostructure can be adjusted by combining with different materials. However, unfortunately, the use of FeOOH-based catalysts for large currents (≥500mAcm -2 )The industrial application of OER remains a huge challenge, and most of the reported heterostructures are constructed under cumbersome synthesis processes and harsh reaction conditions such as high temperature (≥100°C) and high pressure. Therefore, it is urgent to develop a low-energy, low-cost, and simple manufacturing method to prepare FeOOH-based catalysts. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a simple strategy based on corrosion and immersion engineering to manufacture MOF-derived NiCo-OH / FeOOH heterostructure nanosheets, and the preparation method thereof comprises the following steps:

[0005] a. In-situ growth of Co-ZIF-L nanosheets on substrate materials by immersion method:

[0006] After Co(NO3)2·6H2O (cobalt nitrate hexahydrate) solution and 2-MeIm (2-methylimidazole) solution are fully mixed, a pretreated substrate material is immersed therein and aged for 4-12 hours, the substrate material on which purple Co-ZIF-L is in situ grown is taken out and washed with ethanol and deionized water several times, and then vacuum dried at 60-80°C to obtain the substrate material on which Co-ZIF-L nanosheets are in situ grown;

[0007] b. Synthesis of NiCo-OH nanosheets:

[0008] Transferring the Ni(NO3)2·6H2O solution and a substrate material precursor for in-situ growth of Co-ZIF-L nanosheets prepared in step a to a reaction kettle, performing a low-temperature hydrothermal reaction at 80-120°C for 3-12 hours, cooling to room temperature, washing the substrate material with ethanol and deionized water for several times, and then vacuum drying at 60-80°C to obtain a substrate material for in-situ growth of NiCo-OH nanosheets;

[0009] c. Synthesis of NiCo-OH / FeOOH nanosheet composites

[0010] The substrate material of the in-situ grown NiCo-OH nanosheets prepared in step b is immersed in a FeSO4·7H2O solution at 25°C to generate NiCo-OH / FeOOH, and then the substrate material is taken out and vacuum dried at 60-80°C to obtain a substrate material loaded with NiCo-OH / FeOOH nanosheets, thereby obtaining a NiCo-OH / FeOOH nanosheet composite material.

[0011] Furthermore, in step a, the concentration of the Co(NO3)2·6H2O solution is 0.05 mmol / mL, and the concentration of the 2-MeIm solution is 0.4 mmol / mL.

[0012] Furthermore, the substrate material described in step a is nickel foam, and the pretreatment process is to clean the nickel foam with acetone and hydrochloric acid solution in sequence.

[0013] Preferably, the aging time in step a is 4 hours.

[0014] Furthermore, the concentration of the Ni(NO3)2·6H2O solution in step b is 2-4 mg / mL.

[0015] Preferably, the concentration of the Ni(NO3)2·6H2O solution in step b is 2 mg / mL.

[0016] Preferably, the temperature of the hydrothermal reaction in step b is 80° C. and the time is 3 h.

[0017] Furthermore, the concentration of the FeSO4·7H2O solution in step c is 5 mg / mL.

[0018] The NiCo-OH / FeOOH nanosheet composite material obtained by the preparation method can be used as a catalytic electrode in an electrochemical water-oxygen separation reaction.

[0019] Working principle of the present invention:

[0020] The present invention constructs a heterogeneous structure in the catalyst, which can not only adjust the electronic structure of the catalyst and optimize the adsorption energy of the reaction intermediates, but also significantly improve the catalytic activity of the catalyst. Due to the synergistic effect between nickel and cobalt, the introduction of the iron heterogeneous structure can further improve the electrocatalytic performance of the transition metal compound in an alkaline solution, thereby achieving the purpose of improving the catalytic activity. The NiCo-OH / FeOOH nanosheet composite electrode material obtained by the present invention has an ultra-thin nanosheet structure, provides a larger electrochemical active area and abundant exposed active sites, and due to the synergistic effect between NiCo-OH and FeOOH, its kinetics are improved, ion transport is enhanced, and the intrinsic catalytic activity is improved.

[0021] Beneficial effects of the present invention:

[0022] The present invention is based on a facile strategy of etching and immersion engineering to fabricate MOF-derived NiCo-OH / FeOOH heterostructure nanosheets. The present invention selects cobalt nitrate as the cobalt source and synthesizes the Co-ZIF-L precursor by a wet chemical method, which involves a room temperature reaction between 2-methylimidazole and cobalt nitrate hexahydrate solution. Secondly, the present invention uses a ZIF-based precursor (Co-ZIF-L) with a smooth leaf-like nanosheet array as a MOF-derived self-sacrificial template, which is added to a nickel nitrate solution for an etching-recombination reaction to form NiCo-OH nanosheets. NiCo-OH is Ni 2+ and Co 2+ ions were synthesized under mild hydrothermal conditions (80 °C), which is lower than the typical hydrothermal synthesis temperature, thus saving energy. Finally, NiCo-OH was immersed in FeSO4·7H2O solution at room temperature and 2+ Etching to generate NiCo-OH / FeOOH composite electrode material. The electrode material exhibits excellent OER activity at 1000 mA cm in alkaline medium. -2The overpotential is only 306mV at a current density of 1.38kV and the Tafel slope is as low as 38mV dec. -1 , which is better than the commercial catalyst RuO2, and shows excellent stability under the 100h chronopotentiometry test. The preparation process of the composite electrode material is simple, the raw materials are abundant, and the cost is low. At the same time, the method of the present invention can be extended to the modification of other transition metal compounds, providing a new guiding idea for the preparation of highly active and highly stable OER electrocatalysts in alkaline environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 1 is the XRD spectrum of the precursor NiCo-OH and NiCo-OH / FeOOH electrodes prepared in the examples of the present invention.

[0024] Figure 2 : is a low-magnification SEM photograph of the NiCo-OH / FeOOH electrode prepared in the example of the present invention.

[0025] Figure 3 TEM image of the NiCo-OH / FeOOH electrode prepared in the embodiment of the present invention.

[0026] Figure 4 This is a high-resolution TEM image of the NiCo-OH / FeOOH electrode prepared in the example of the present invention.

[0027] Figure 5 This is the full XPS spectrum of the NiCo-OH / FeOOH electrode prepared in the example of the present invention.

[0028] Figure 6 This is the Ni 2p high-resolution XPS spectrum of the NiCo-OH / FeOOH electrode prepared in the example of the present invention.

[0029] Figure 7 : This is the Co 2p high-resolution XPS spectrum of the NiCo-OH / FeOOH electrode prepared in the example of the present invention.

[0030] Figure 8 : This is the Fe 2p high-resolution XPS spectrum of the NiCo-OH / FeOOH electrode prepared in the example of the present invention.

[0031] Fig. 9 This is the O1s high-resolution XPS spectrum of the NiCo-OH / FeOOH electrode prepared in the embodiment of the present invention.

[0032] Fig.10 : This is the OER polarization curve of the NiCo-OH / FeOOH electrode prepared in the example of the present invention and commercial RuO2 in 1M KOH solution.

[0033] Fig.11 : is the Tafel slope of the NiCo-OH / FeOOH electrode prepared in the example of the present invention and commercial RuO2 in 1M KOH solution.

[0034] Fig.12 1 is the chronopotentiometry curve of the NiCo-OH / FeOOH electrode prepared in the embodiment of the present invention in 1M KOH solution. DETAILED DESCRIPTION

[0035] Embodiment 1,

[0036] This embodiment provides a method for preparing a NiCo-OH / FeOOH heterostructure nanosheet, comprising the following steps:

[0037] a. In-situ growth of Co-ZIF-L nanosheets on nickel foam by immersion method:

[0038] Dissolve 2mmol of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 16mmol of 2-methylimidazole (2-MeIm) in 40mL of deionized water to prepare a precursor solution. Mix the two precursor solutions, stir for 1h to mix thoroughly, immerse a piece of pretreated nickel foam washed with acetone and hydrochloric acid solution in it, and age it for 4 hours. Take out the nickel foam with in-situ growth of purple Co-ZIF-L, wash it with ethanol and deionized water several times, and then vacuum dry it at 60-80℃ overnight to obtain the nickel foam precursor with in-situ growth of Co-ZIF-L nanosheets;

[0039] b. Synthesis of NiCo-OH nanosheets:

[0040] NiCo-OH nanosheets were synthesized by a one-step low-temperature hydrothermal method. Specifically, 40 mg of Ni(NO3)2·6H2O was first dissolved in 20 mL of deionized water and stirred to obtain a transparent solution. The obtained solution and the nickel foam precursor of the in-situ grown Co-ZIF-L nanosheets prepared in step a were then transferred to a 50 mL reactor and subjected to a low-temperature hydrothermal reaction at 80°C for 3 hours. After cooling to room temperature, the nickel foam was taken out and washed several times with ethanol and deionized water, and then vacuum dried at 60-80°C overnight to obtain nickel foam of in-situ grown NiCo-OH nanosheets.

[0041] c. Synthesis of NiCo-OH / FeOOH nanosheet composites

[0042] NiCo-OH / FeOOH is synthesized by an immersion method. Specifically, the nickel foam with in-situ grown NiCo-OH nanosheets prepared in step b is immersed in 10 mL of a solution containing 50 mg of FeSO4·7H2O at 25° C. for 1 hour to generate NiCo-OH / FeOOH, and then the nickel foam is vacuum dried at 60-80° C. overnight to obtain a nickel foam loaded with NiCo-OH / FeOOH nanosheets, thereby obtaining a NiCo-OH / FeOOH nanosheet composite material.

[0043] Embodiment 2,

[0044] In this example, the NiCo-OH / FeOOH nanosheet composite material prepared by the above method is used as a catalytic electrode to perform an electrochemical test, including the following steps:

[0045] (1) Preparation of working electrode:

[0046] The nickel foam loaded with NiCo-OH / FeOOH nanosheets was cut into a size of 0.5 cm × 1 cm and used as the working electrode of the oxygen evolution reaction catalyst;

[0047] Commercial RuO2 powder was dissolved in a mixed solution of 960 μL deionized water and 40 μL naphthol, and after ultrasonication for 30 min, it was evenly dropped on the nickel foam and dried at room temperature to obtain a catalyst-loaded working electrode.

[0048] (2) The electrochemical test was carried out in a standard three-electrode test system, with the two electrodes prepared in step (1) as working electrodes, Ag / AgCl as reference electrode, carbon rod as counter electrode, and 1 M KOH solution as electrolyte;

[0049] (3) Using NiCo-OH / FeOOH electrode as the working electrode, electrochemical tests were performed on a CHI660B electrochemical workstation at room temperature;

[0050] For the OER stability test, the current density was kept at 1000 mA cm by chronopotentiometry. -2 Under these conditions, the change of potential over time was recorded.

[0051] The crystal structures of NiCo-OH and NiCo-OH / FeOOH composite electrodes were analyzed by X-ray diffraction (XRD). Figure 1As shown, the peaks of NiCo-OH and FeOOH (JCPDS No.: 29-0713) coexist in the NiCo-OH / FeOOH electrode, indicating the coexistence of the two. For the NiCo-OH catalyst, the peak is located between the characteristic peaks of β-Co(OH)2 (JCPDS 74-1057) and β-Ni(OH)2 (JCPDS14-0117). This confirms that both nickel and cobalt are incorporated into the hydroxide phase to form NiCo-OH.

[0052] The morphology and structure of the NiCo-OH / FeOOH composite electrode were analyzed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 2 As shown in Figure 3, NiCo-OH / FeOOH exhibits a unique nanoarray assembled by interconnected ultrathin nanosheets. These nanosheets form a disordered and loose nanostructure, which increases the contact area with the electrolyte and has abundant open spaces and electrochemically active sites. Figure 3 The TEM image of the NiCo-OH / FeOOH composite electrode is shown, and it can be found that it also exhibits a thin-sheet structure at the microscopic level. Figure 4 This is a high-resolution TEM image of the NiCo-OH / FeOOH composite electrode. The lattice fringes with a spacing of 0.236 nm correspond to the (011) crystal plane of NiCo-OH, while the lattice fringes with a spacing of 0.203 nm correspond to the (220) crystal plane of FeOOH.

[0053] X-ray photoelectron spectroscopy (XPS) was used to analyze the elemental composition and chemical state of the NiCo-OH / FeOOH composite electrode. Figure 5 The XPS full spectrum shows the presence of Ni, Co, O and Fe elements. Figure 6 The XPS high-resolution spectrum of Ni 2p. For NiCo-OH / FeOOH, the Ni 2p3 / 2 and Ni 2p1 / 2 peaks are located at 856.5 and 874.3 eV, respectively, and there are two satellite peaks, indicating that Ni 2+ Oxidation state. Figure 7 This is the XPS high-resolution spectrum of Co 2p. For the Co 2p spectrum of NiCo-OH / FeOOH, the Co 2p3 / 2 and Co 2p1 / 2 peaks at 781.4 and 797.1 eV, as well as two satellite peaks at 786.0 and 797.1 eV can be observed. These two peaks are consistent with the Co(OH)2 reported in the literature. Figure 8 This is the XPS high-resolution spectrum of Fe 2p. The peaks at 711.6 and 724.3 eV correspond to Fe 2p3 / 2 and Fe2p1 / 2, respectively, indicating the typical Fe 3+ Oxidation state. Fig. 9This is the XPS high-resolution spectrum of O1s. The O 1s spectrum clearly shows three characteristic peaks at 530.6, 531.5 and 532 eV, which are attributed to oxides, metal hydroxide groups and adsorbed oxygen, respectively.

[0054] At room temperature, the electrochemical performance of the NiCo-OH / FeOOH electrode was tested: Fig.10 It can be seen that at a current density of 1000 mA cm -2 When the overpotential of NiCo-OH / FeOOH composite electrode is only 306mV, which is much smaller than the overpotential of commercial RuO2. Fig.11 It can be seen that the NiCo-OH / FeOOH electrode not only has a lower overpotential, but also has the lowest Tafel slope of only 38 mV dec. -1 .like Fig.12 As shown, at 1000mA cm -2 The NiCo-OH / FeOOH composite electrode showed excellent stability without obvious decrease in current density after 100 h of chronopotentiometry test.

[0055] In summary, the present invention provides a simple strategy based on corrosion and immersion engineering to manufacture MOF-derived NiCo-OH / FeOOH heterostructure nanosheet composite electrodes. The ultra-thin nanosheet structure of the composite material provides abundant active sites, and the synergistic effect of NiCo-OH and FeOOH improves the kinetics and ion transport, thereby improving its electrocatalytic activity. The present invention can also be extended to the heterostructure design of other transition metal compounds, providing new ideas for the development of efficient and economical OER catalysts.

Claims

1. A method for preparing NiCo-OH / FeOOH heterostructure nanosheets, characterized in that: The steps include: a. In-situ growth of Co-ZIF-L nanosheets on substrate materials by immersion method: After the Co(NO3)2·6H2O solution and the 2-MeIm solution are fully mixed, a pretreated substrate material is immersed therein and aged for 4-12 hours, the substrate material on which the purple Co-ZIF-L is in situ grown is taken out and washed with ethanol and deionized water several times, and then vacuum dried at 60-80°C to obtain the substrate material on which the Co-ZIF-L nanosheets are in situ grown; b. Synthesis of NiCo-OH nanosheets: Transferring the Ni(NO3)2·6H2O solution and the substrate material of the in-situ grown Co-ZIF-L nanosheets prepared in step a to a reaction kettle, performing a low-temperature hydrothermal reaction at 80-120°C for 3-12 hours, cooling to room temperature, washing the substrate material with ethanol and deionized water for several times, and then vacuum drying at 60-80°C to obtain the substrate material of the in-situ grown NiCo-OH nanosheets; c. Synthesis of NiCo-OH / FeOOH nanosheet composites The substrate material of the in-situ grown NiCo-OH nanosheets prepared in step b is immersed in a FeSO4·7H2O solution at 25°C to generate NiCo-OH / FeOOH, and then the substrate material is taken out and vacuum dried at 60-80°C to obtain a substrate material loaded with NiCo-OH / FeOOH nanosheets, thereby obtaining a NiCo-OH / FeOOH nanosheet composite material.

2. The method for preparing a NiCo-OH / FeOOH heterostructure nanosheet according to claim 1, characterized in that: In step a, the concentration of Co(NO3)2·6H2O solution is 0.05 mmol / mL, and the concentration of 2-MeIm solution is 0.4 mmol / mL.

3. The method for preparing a NiCo-OH / FeOOH heterostructure nanosheet according to claim 1, characterized in that: The substrate material described in step a is nickel foam, and the pretreatment process is to wash the nickel foam with acetone and hydrochloric acid solution in sequence.

4. The method for preparing a NiCo-OH / FeOOH heterostructure nanosheet according to claim 1, characterized in that: The aging time in step a is 4 hours.

5. The method for preparing a NiCo-OH / FeOOH heterostructure nanosheet according to claim 1, characterized in that: The concentration of the Ni(NO3)2·6H2O solution in step b is 2-4 mg / mL.

6. The method for preparing a NiCo-OH / FeOOH heterostructure nanosheet according to claim 1, characterized in that: The concentration of Ni(NO3)2·6H2O solution in step b is 2 mg / mL.

7. The method for preparing a NiCo-OH / FeOOH heterostructure nanosheet according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step b is 80° C. and the time is 3 h.

8. The method for preparing a NiCo-OH / FeOOH heterostructure nanosheet according to claim 1, characterized in that: The concentration of the FeSO4·7H2O solution in step c is 5 mg / mL.

9. A NiCo-OH / FeOOH heterostructure nanosheet, characterized in that: Prepared according to any one of claims 1 to 8.

10. The use of a NiCo-OH / FeOOH heterostructure nanosheet according to claim 9, characterized in that: NiCo-OH / FeOOH nanosheet composites were used as catalytic electrodes in the electrochemical water separation and oxygen reaction.

Citation Information

Cited By

  • FeCoNi-NS-ACVs catalyst with high-activity oxygen evolution reaction and preparation method of FeCoNi-NS-ACVs catalyst

    CN119877021A